Design and Development of a Biology Learning Website to Improve Biological Literacy on Human Reproductive System Topics - Muhamad, Admiral; Ristanto, Rizhal Hendi; Dewahrani, Yulilina Retno (Journal Of Biology Education Research (JBER), 2025)
The use of appropriate media is an important factor in improving student understanding in biology learning. One of the essential skills that need to be developed through biology learning is biological literacy, which includes nominal, functional, structural, and multidimensional aspects as a basis for understanding concepts in depth. Therefore, learning media designed based on biological literacy principles has the potential to effectively improve students' biological literacy skills. The purpose of this study was to develop and produce effective website-based learning media that aligns with the principles of the Merdeka Curriculum to improve students' biological understanding and literacy in the topic of the human reproductive system. This study used a modified ADDIE model, with emphasis on the Analysis, Design, and Development phases. Data collection instruments consisted of needs analysis, expert validation of language, content, and media by two experts, and readability testing conducted by two biology teachers and participating students. Descriptive analysis was used to interpret the data. The validation results showed that the media obtained high scores in all evaluated aspects (language, content, and media) which were included in the very valid category. Readability tests by teachers and students also showed very valid results. It can be concluded that this web-based learning media meets the quality and effectiveness standards that have been set in the learning design so that it is considered suitable for use in the learning process.